The Implementation of the Ba’i Istisna Principle in Online Trading Practices - Sukri; Wargo; Rosli Mokhtar (Zabags International Journal of Islamic Studies, 2025)
The digital transformation of the commercial sector has encouraged communities to adopt online trading systems, including in Kelurahan Talang Babat, where the practice of ordering goods based on specific customer requirements has become increasingly common. In this context, the Ba’i Istisna contract, as a form of Islamic legal agreement that allows for the production of goods upon request, emerges as a relevant and applicable mechanism. This study aims to examine how the implementation of Ba’i Istisna in online transactions influences consumer trust and to identify the challenges encountered in its application. Employing a qualitative approach with a phenomenological strategy, data were collected through field observations and in-depth interviews with business actors and consumers, and then analyzed thematically using triangulation techniques. The findings reveal that contract transparency, clarity of product specifications, and seller accountability are key factors in fostering customer loyalty, while regulatory limitations, digital literacy gaps, and technological readiness remain significant barriers to the optimal application of Islamic principles. These results contribute to the development of a community-based sharia-compliant transaction model that is adaptive to digital dynamics and offer a conceptual foundation for local policy formulation and inclusive Islamic economic education.